Mini Symposium ? Ore Reserves: Classification, Calculation And Reporting - A Schema For Classifying And Reporting Mineral Resources: Rationalizing The Needs For Consistency And Accuracy With The Demands For Disclosure - David Harrison (Society for Mining, Metallurgy & Exploration, 1983)
Exxon Minerals Company uses geostatistical techniques for ore resource evaluation of its mineral projects. These techniques provide the most reliable estimates of recoverable tonnage and grade and uniform and realistic confidence limits. A schema has been developed which categorizes the company's successive evaluation phases. Clear separation is intended between geostatistical estimates and other factors in project evaluation such as mining, metallurgy, and economics. Company management seeks consistent and reliable estimates for investment decision-making and to meet growing demands for disclosure of mineral assets.